ANALISIS EFISIENSI PRODUKSI DAN PENGELOLAAN LIMBAH PADA PABRIK SEPATU: STUDI KASUS DI JL. BROMO KOTA MEDAN, SUMATERA UTARA - Ayunda Syapa Azra; Dina Wenika; Muhammad Zieo Addefrid Putra; Zainarti Zainarti (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to analyze production efficiency and waste management in a shoe factory located on Jl. Bromo. A case study approach is used to explore the production process and the waste management strategies implemented. Data was collected through direct observation, interviews with management, and analysis of related documents. The research results showed that the factory had several inefficiencies in the production chain, which resulted in wastage of raw materials and energy. In addition, the existing waste management system does not fully meet applicable environmental standards, especially in terms of hazardous waste processing. Based on these findings, it is recommended that factories make improvements to production technology and improve waste management practices through implementing the 3R (reduce, reuse, recycle) system. Implementation of this strategy is expected to increase operational efficiency and environmental sustainability.